THE GROWTH OF TWO MARINE-MICROALGAE (Chaetoceros gracilis and Tetraselmis chuii ) IN SEMI-CON TINUOUS CULTURE METHOD - Subandiyono . (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The growth performance of two marine-microalgal species, i.e. a centric diatom- Chaetoceros gracilis and a green algae- Tetraelmis chui, were investigated. Semi continuous- 200 litre plastic bag facilitated with a 0.2 mm hydrophobic filter membrane for each were required to culture each species of the microalgae. Aseptical method was employed during algal culture, harvesting, and refilling. The algal density in the bag culture was monitored every 2 days. Results indicated that the average value of mean generation time for C. gracilis and T. chui were 18.83 and 25.14 hours, respectively. The average value of bacterial counts taken from inoculated C. gracilis and T. chui culture samples were 9.9 x 10E6 and          7.8 x 10E4 bacteria ml media. The importance of bacterial monitoring in relation to recommended culture method is discusses briefly.